VD_FINDINFO HC / 2024 / 168 vom 8. März 2024 - VD Tribunal cantonal (2024)
ADMISSION DE LA DEMANDE, EXPULSION DE LOCATAIRE, FÉRIES JUDICIAIRES, CAS CLAIR, LOGEMENT DE LA FAMILLE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 266n CO, 86 al. 1 CO, 86 CO, 257 al. 1 CPC (CH), 257 al. 1 let. a CPC (CH), 257 al. 1 let. b CPC (CH), 257 CPC (CH)